Natural two-view learning - Rastogi, Raghav (2013)
Semi-supervised learning has attracted a lot of attention because in many data mining applications, unlabelled training examples are easily available, but labelled training examples are costly to attain. In this report, the MATLAB implementation of a new co-training style semi-supervised algorithm, named tri-training, has been discussed. Tri-training does not require adequate and redundant views. It also does not partition the instance space into equivalence classes. Hence, it can be used for a wide range of data mining applications.